Space-time image reconstruction algorithm for diverse ultrasound transducer element distributions - Lee, M.; Singh, R.S.; Culjat, M.O.; Natarajan, S.; Cox, B.P.; Brown, E.R.; Grundfest, W.S.; Hua Lee (2009 IEEE International Symposium on Biomedical Imaging: From Nano to Macro, 2009)
The standard architecture of a medical ultrasound transducer is a linear phased array of piezoelectric elements in a compact, hand-held form. Acoustic energy not directly reflected back towards the transducer elements during a transmit-receive cycle amounts to lost information. An ultrasound imaging system currently in development seeks to maximize the collection of reflected signals with a large, flexible transducer array which conforms to contours of the subject's body, resulting in more directional look angles and an increase in received image data. However in this design, element distributions are irregular and an organized arrangement may no longer be maintained. This paper presents a versatile space-time image reconstruction algorithm designed for this system, operating in a step FMCW modality. Simulated images are included which demonstrate the algorithm's flexibility in application, and the effects of transducer aperture size and operating bandwidth on resolving capability.